(untitled) (Research, Society and Development, 2023)
Onchocerciasis, a disease caused by Onchocerca volvulus is transmitted via hematophagous Diptera of the genus Simulium, also known as “black flies” or “borrachudos”. This disease develops in humans and can cause onchocerciatic dermatitis, in addition to progressing to blindness, a fact that justifies being popularly known as “river blindness”. It is listed in the group of Neglected Tropical Diseases and has its eradication goal the year 2025. The aim of this study was to evaluate the incidence of river blindness in the Yanomami and Ye`kwana Indigenous Territory, the main focus of concentration of this disease in the Americas. For this, a literature review was carried out in the Medline, PubMed and Scielo databases, in addition to the national epidemiological bulletins. In this study, it was observed that among the Yanomami this disease is considered endemic and, despite several control programs launched locally and worldwide, these indigenous groups continue to present cases of the disease, due to the difficulty of indigenous health services in accessing indigenous groups. to provide adequate preventive coverage of the entire population, as well as sociocultural aspects marked by the territorial mobility that characterizes this ethnic group. The problem with this disease is the presence of subcutaneous nodules, skin rash, geroderma and blindness. Therefore, the persistence of onchocerciasis among Yanomamis is highlighted, who continue to face problems due to onchocerciasis, which are constantly neglected by Brazilian public health.